A Mutation in DAOA Modifies the Age of Onset in PSEN1 E280A Alzheimer's Disease. (5th January 2016) - Vélez, Jorge I.; Rivera, Dora; Mastronardi, Claudio A.; Patel, Hardip R.; Tobón, Carlos; Villegas, Andrés; Cai, Yeping; Easteal, Simon; Lopera, Francisco; Arcos-Burgos, Mauricio
Abstract : We previously reported age of onset (AOO) modifier genes in the world's largest pedigree segregating early-onset Alzheimer's disease (AD), caused by the p.Glu280Ala (E280A) mutation in the PSEN1 gene. Here we report the results of a targeted analysis of functional exonic variants in those AOO modifier genes in sixty individuals with PSEN1 E280A AD who were whole-exome genotyped for 250, 000 variants. Standard quality control, filtering, and annotation for functional variants were applied, and common functional variants located in those previously reported as AOO modifier loci were selected. Multiloci linear mixed-effects models were used to test the association between these variants and AOO. An exonic missense mutation in the G72 ( DAOA ) gene (rs2391191, P = 1.94 × 10 −4, P FDR = 9.34 × 10 −3 ) was found to modify AOO in PSEN1 E280A AD. Nominal associations of missense mutations in the CLUAP1 (rs9790, P = 7.63 × 10 −3, P FDR = 0.1832) and EXOC2 (rs17136239, P = 0.0325, P FDR = 0.391) genes were also found. Previous studies have linked polymorphisms in the DAOA gene with the occurrence of neuropsychiatric symptoms such as depression, apathy, aggression, delusions, hallucinations, and psychosis in AD. Our findings strongly suggest that this new conspicuous functional AOO modifier within the G72 ( DAOA ) gene could be pivotal for understanding the genetic basis of AD.